SLIPPING INTO THE SHADOWS OF KYAI’S FIGURES: WOMEN PARTICIPATION IN INDONESIAN PESANTREN’S WEB OF POWER - Elfira, Mina (International Review of Humanities Studies, 2019)
This paper explores women‟s efforts in challenging male authority within Indonesian pesantren (Islamic education institution). Historically, pesantren tradition did not involved women in its social and religious affairs, and the full authority was in the hand of Kyai (owner and leader of Pesantren). Later on, women, through figures of Nyai (wife, or daughters of Kyai), have started to get involve in pesantren‟s life by helping Kyai in managing pesantren‟s daily life, especially, in taking care of female santri (students). The paper investigates what kind of negotiations, conducted by these women, in dealing with pesantren‟s patriarchal attitude so they can more participate in its „public” and authority matters. Based on a qualitative research data, collected from fieldwork in selected pesantren around Indonesia, this paper argues that in order to maximize their contribution in pesantren web of power, pesantren women as Nyai actively try in any ways to change patriarchal concepts, to empower themselves, and to negotiate social changes.